MEKANISME PENCATATAN KONTRIBUSI PADA PT. ASURANSI ASKRIDA SYARIAH PALANGKA RAYA BERDASARKAN PSAK 108 - Rahmad Kurniawan; Sri Ulfa (Pusat Riset dan Inovasi Nasional, 2021)
This article aims to analyze the mechanism and adjust the recording of sharia insurance contribution funds with PSAK 108 at PT. Askrida Syairah Palangka Raya Insurance. Research Methods: This research is a field research using qualitative research methods with a descriptive approach, while the subject of this research is the Head of the Office of PT. Askrida Syariah Palangka Raya Insurance regarding the mechanism for recording sharia insurance contribution funds. Data collection techniques in this study used observation, interviews and documentation techniques. The data validation technique uses the credibility test (internal validity) with technical triangulation and dependability tests. Research Findings: The results of this study indicate that 1) the mechanism for recording contribution funds at PT. Askrida Syariah Palangka Raya Insurance in terms of determining the contribution value is influenced by the contribution rate, loan value and administrative costs. Then in terms of the distribution of contributions, Bank Syariah Indonesia gets 15% as Ujrah Bank and the remaining 60% goes into the participant's account as tabarru' funds and 40% goes to the manager's account as ujrah funds. 2) Recording of contribution funds at PT. Askrida Syariah Palangka Raya Insurance is not fully compliant with PSAK 108. Renewal of Research: PT. Askrida Syariah Palangka Raya Insurance in terms of contribution sharing is not only distributed to companies and managers but the Bank also gets a 15% share as the Bank's ujrah in managing contribution funds.